(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Conventional agricultural practices, such as burning or discarding rice straw, contribute to environmental degradation, highlighting the need for sustainable alternatives like zero-waste utilization. This study aimed to convert rice straw into organic fertilizer, reduce reliance on chemical fertilizers, and promote sustainable agriculture in Rilau Ale District, Bulukumba Regency. Through a community-based program, farmers were trained in waste-processing techniques using simple technologies. The results showed that 85% of participants adopted the method, eliminating straw burning while improving soil fertility and reducing chemical fertilizer use. This initiative demonstrates that zero-waste straw management is a replicable model for advancing agricultural sustainability and environmental resilience.